KAJIAN KINERJA AGRIBISNIS STARWBERRY ORGANIK Study Kasus Kelompok Tani Kina Kelurahan Rurukan dan Kelompok Tani Agape Kelurahan Rurukan Satu - Marlen M. Rumengan; Tommy F. Lolowang; Agnes E. Loho; Charles R. Ngangi (COCOS, 2015)
ABSTRACT Agribusiness as the overall activity of the means of production and distribution of farm production, farming activities, as well as storage, processing, distribution of farm commodities, and other activities that make up the product. Agribusiness is a system consisting of sub-systems are interlinked with each other. The subsystem is agroinput, agroproduction, agro-industry, Agroniaga and argroservice. This study aims to determine the performance of agribusiness in farmer groups in Sub Rurukan quinine and farmer groups in the Village agape Rurukan One. The research was conducted from june to August 2014 and data using survey methods. Data collected consist of primary data and secondary data. Primary data is data obtained from interviews with respondents based on a list of questions (questioner), while secondary data obtained from the relevant agencies Rurukan sub-district Office and District Office Rurukan One. Data analysis using descriptive analysis and to determine the performance of the system using a ranking scale agribusiness. The results showed that the performance of agribusiness is between 60-80 value, so it gets the final value 72 thus value indicates that the relatively high performance of agribusiness Â Key words: Agribusiness performance, farmer group, RurukanÂ